TYPES OF AGGRESSIVE BEHAVIOR AMONG LEARNERS WITH MODERATE INTELLECTUAL DISABILITY IN NIGERIA AS PERCEIVED BY TEACHERS - Udeme Samuel Jacob; Jace Pillay; Esther Olufunke Oyefeso (Universitas Islam Negeri (UIN) Mataram, 2021)
This study examined aggressive behavior (verbal aggression, physical assault, socially unacceptable and destructive behavior) among learners with moderate intellectual disability in south-western Nigeria, through teachers’ perceptions. The study used a descriptive survey design. Convenient sampling technique was used to select respondents (87 teachers of pupils with intellectual ability in private and public schools in south West Nigeria). The aggressive behavior scale (ABS) was used to elicit responses. Data retrieved was analysed using descriptive and inferential statistics. Results showed that teachers’ perception of the developmental trend of aggressive behavior among learners with moderate intellectual disability was significant (T = 44.385, Mean Difference = 3.115 while p < .05). Also, there was no significant gender difference in verbal aggressive (F=0.997, p>.05), physical aggressive (F=3.628, p>.05), socially unacceptable aggressive (F=1.233, p>.05), and destructive behavior (F=0.571, p>.05). Interventions should be in line with these.